THE ROLE OF THE NEIGHBORHOOD AUTHORITY IN RAISING RESIDENTS’ OBEDIENCE TO THE IMPLEMENTATION OF THE HEALTH PROTOCOLS DURING THE COVID-19 PANDEMIC - Rembulan, Cicilia Larasati; Rahmawati, Kuncoro Dewi; Eunike, Prisca; Dorkas, Mopheta Audiola; Dewi, Clara Hosana Yessica Jelita; Wijaya, Feilicya Aurellia (Faculty of Psychology Universitas Islam Sultan Agung Semarang, 2023)
Public obedience to the implementation of the health protocols during the COVID-19 pandemic was important. In reality, not all people, especially in residential areas (neighborhoods), were obedient. Limited research had addressed the implementation of health protocols in the settings of the neighborhood so a thorough study on this issue was significant to explore new knowledge. This study aimed to identify the authorities in charge of handling the COVID-19 pandemic in the neighborhoods, the obstacles experienced by the authorities and the residents, the support of the neighborhood authorities, the residents’ responses to policies related to the pandemic, and the impacts of the pandemic on the residents’ lives. There were 30 participants from 30 neighborhoods interviewed and observed. To increase the credibility of the study, a triangulation method was employed. It revealed that there were formal and informal authorities. Both the authorities and the residents experienced obstacles. The authorities had conducted many efforts to handle the pandemic like delivering education, providing facilities, modifying the residents’ behaviors, and collaborating with related stakeholders. Residents were supporting and not supporting the policies and the authorities’ efforts. Besides the negative impacts on the economy, health, society, and psychology, it turned out the pandemic has also brought positive impacts such as the adaptation to new habits and the emergence of new micro-businesses in the neighborhoods.